Resurrecting Leonora Piper: How Science Discovered the Afterlife by Michael Tymn - Morse, Philip S. (Journal of Scientific Exploration, 2013)
This isa book that offers many of the recorded transcripts of Leonora Piper’s mediumship experiences with various sitters starting in 1885 when William James began taking an interest in her. According to the author, it is an "attempt to explain the dynamics of her mediumship, including the difficulties associated with it, and to offer some of the best evidence for survival of consciousness after death that came from her mediumship." (p. xv) The sessions with Mrs. Piper took place in both England and the United States over a period of 25 years. They numbered in the hundreds and were observed and recorded by many of the most distinguished scientists and academicians of the day, including Richard Hodgson, William James, Sir Oliver Lodge, Frederic Myers, and Professor James Hyslop. The intent was to offer as much evidence as possible to either support or refute the nature of mediumistic communications and whether they truly come from discarnate entities. The vigor and amount of time and energy that went into examining Mrs. Piper was unprecedented. Many of the most distinguished scholars, most of them initially intent on exposing Mrs. Piper as a fraud, took their research very seriously and subjected Piper to the highest standards of vigorous scrutiny. In addition to determining whether conscious fraud was involved, the researchers were also interested in determining whether Piper got her results through telepathy or “super-psi.”